Internalizing Religious Moderation Through the Religious Curriculum at PGRI 2 Vocational School, Kediri - M Hayat HF; Imam Taulabi; Syafik Ubaidila; Fahrul Rozi (Penerbit Presisi Pustaka, 2026)
This study aims to describe the implementation of religious moderation internalization through the religious education curriculum at SMK PGRI 2 Kediri, examine students' understanding of religious moderation, and identify both supporting and inhibiting factors in the process. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation. The findings reveal that the internalization of religious moderation has been systematically carried out through religious instruction that is adaptive to the diverse religious backgrounds of students, including those from Christian, Catholic, and Hindu faiths. The 2013 curriculum plays a crucial role by embedding core values such as tolerance, peace, and respect for diversity. Students demonstrate a good understanding of religious moderation, reflected in their tolerant attitudes and respectful behavior toward peers of different religions. This success is supported by active teacher involvement, curriculum alignment, and a conducive family environment. However, challenges remain, particularly the negative influence of social media and the limited number of qualified religious educators. These findings highlight the need for cross-sector collaboration to sustain and enhance the internalization of religious moderation in education